2019
DOI: 10.1167/iovs.19-26994
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Utility of Fundus Autofluorescence in Congenital Aniridia Using Scanning Laser Ophthalmoscopy

Abstract: PURPOSE. To investigate fundus autofluorescence (FAF) and other fundus manifestations in congenital aniridia. METHODS. Fourteen patients with congenital aniridia and 14 age-and sex-matched healthy controls were examined. FAF images were obtained with an ultra-widefield scanning laser ophthalmoscope. FAF intensity was quantified in the macular fovea and in a macular ring surrounding fovea and related to an internal reference within each image. All aniridia patients underwent an ophthalmologic examination, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Heidelberg Spectralis OCT2 (Heidelberg Engineering GmbH, Heidelberg, Germany) was used to acquire spectral-domain optical coherence tomography (SD-OCT) scans of the macular region as described previously (512–1536 A-scans/B-scans, 49 B-scans over 20° × 20° or 30° × 10°; 30° × 5° for normal controls). 17 , 23 The built-in eye-tracking system was used to compensate for eye-motion artifacts and 5–20 horizontal B-scans were averaged during imaging. The participants’ head posture and gaze direction were adjusted to minimize the amplitude of nystagmus during OCT imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Heidelberg Spectralis OCT2 (Heidelberg Engineering GmbH, Heidelberg, Germany) was used to acquire spectral-domain optical coherence tomography (SD-OCT) scans of the macular region as described previously (512–1536 A-scans/B-scans, 49 B-scans over 20° × 20° or 30° × 10°; 30° × 5° for normal controls). 17 , 23 The built-in eye-tracking system was used to compensate for eye-motion artifacts and 5–20 horizontal B-scans were averaged during imaging. The participants’ head posture and gaze direction were adjusted to minimize the amplitude of nystagmus during OCT imaging.…”
Section: Methodsmentioning
confidence: 99%
“…In a different prospective study, ONH was observed in four of 14 patients (29%). 85 In this latter study, ONH was more frequent in patients with foveal hypoplasia grade or than in those with either grade 0, or 2. This suggests that ONH coincides with more severe foveal hypoplasia.…”
Section: Optic Nervementioning
confidence: 60%
“…This correlation has also been found in other studies.20, 85 Furthermore, there is an association between impaired red-green color vision and increasing grade of foveal hypoplasia.125 OCT images of aniridia patients with different grades of foveal hypoplasia have previously been published. 85,125,126 Central foveal thickness is increased in aniridia,20, 70, 126 either compared to healthy controls in the same study,126 or to previously published normal values.20, The total length of the outer nuclear layer and the Henle fiber layer in fovea is, however, shorter in aniridia patients than in controls.126 Additionally, the outer segments of the foveal cones are shorter in aniridia. Pedersen and coworkers also reported that aniridia patients with mutations in coding regions of the PAX6 gene have thinner outer retinal layers in the fovea than those with mutations in noncoding regions of the gene.…”
Section: Lens Coloboma Microspherophakia and Posterior Lenticonusmentioning
confidence: 86%
“…The absence of FAZ may be detected in fundus autofluorescence (FAF) as the absence of the central hypofluorescent spot. [ 22 ] Landsend et al . (2019) found that the mean intensity of the FAF in macula versus fovea was close to 1 in most aniridia patients.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…(2019) found that the mean intensity of the FAF in macula versus fovea was close to 1 in most aniridia patients. [ 22 ] They also reported that 86% of aniridia patients may have a hypopigmented fundus. This can be attributed to the role of PAX6 in retinal pigment epithelium differentiation.…”
Section: Clinical Featuresmentioning
confidence: 99%